COMPARISON APPROACHES PHILOSOPHY LEAN PRODUCTION AND CONCEPT SYSTEMIC LIMITATIONS OF TOOLS FINANCIAL MANAGEMENT - Рибалка , Дмитро (Socio-economic relations in the digital society, 2019)
The article compares the philosophy of lean production and the concept of systemic constraints in the context of financial management. The principles of these approaches, laid down by their founders Tayichi Ono and Goldratt Moshe Eliyahu, are considered. Factors of careful production (muda) are revealed and analyzed. The flow of value creation is exemplified by the Coca-Cola banks. The peculiarities of the organization of the production process of enterprises using the philosophy of lean manufacturing are considered. The article illustrates the classical management structure of the enterprise and the “elongated structure” used at lean manufacturing enterprises. The novel «Target» is described in detail, which describes the basic principles of the concept of systemic constraints. It is determined that the concept of the systemic constraints of Goldratt Eliyahu is a better analytical tool for enterprise management, has a clear and understandable theoretical basis, easily applicable quantitative models (formulas) with which you can understand what changes are financially effective and which are not.